Logic (or Illogic?) of Japan’s Aversion to TPNW and Charting a Path Forward - Nishida, Michiru (Journal for Peace and Nuclear Disarmament, 2024)
Japan, the only country to have experienced atomic bombs during wartime, is the only one among the US allies to have positively evaluated the Treaty on the Prohibition of Nuclear Weapons (TPNW) at the highest political level, with Prime Minister Kishida saying that as “a very important treaty that can serve an exit as we seek to realize a world without nuclear weapons”. Yet Japan has distanced itself from the TPNW, not participating even as an observer in the TPNW’s Meeting of States Parties. This paper attempts to explain Japan’s stance toward the TPNW process, before and after the formation of the treaty, based on a hypothesis that Japan’s nuclear policy is formed by a balancing act between two factors: humanitarian and security concerns. It then attempts to chart a path forward for any possible engagement between Japan and the TPNW. It argues that a substance-over-formality approach, not sticking to the TPNW formalities but in a framework separate from the TPNW, may open a window of opportunity for cooperation. Japan can also flexibly consider security benefits in engaging with the TPNW and comprehensively calculate possible security benefits and drawbacks without a predetermined conclusion. Since the NPT may not be sustainable unless there is a significant progress in nuclear disarmament, which itself is unlikely, like it or not, the TPNW cannot be ignored indefinitely and the time may come in the not-too-distant future when Japan will eventually have to consider engagement with the TPNW.